2014
DOI: 10.1038/cdd.2014.152
|View full text |Cite
|
Sign up to set email alerts
|

NRF2-driven miR-125B1 and miR-29B1 transcriptional regulation controls a novel anti-apoptotic miRNA regulatory network for AML survival

Abstract: Transcription factor NRF2 is an important regulator of oxidative stress. It is involved in cancer progression, and has abnormal constitutive expression in acute myeloid leukaemia (AML). Posttranscriptional regulation by microRNAs (miRNAs) can affect the malignant phenotype of AML cells. In this study, we identified and characterised NRF2-regulated miRNAs in AML. An miRNA array identified miRNA expression level changes in response to NRF2 knockdown in AML cells. Further analysis of miRNAs concomitantly regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 42 publications
2
53
0
1
Order By: Relevance
“…Grin2b could compete with mmu_circRNA_34132 for binding to mmu-miR-29b-1-5p based on this study. Moreover, Nrf2 could downregulate miR-29b-1 through binding to specific ARE sites [53]. These findings suggested that mmu_circRNA_34132-mmu-miR-29b-1-5p-Grin2b interaction might play a role in neurodegenerative diseases that are regulated by Nrf2.…”
Section: Discussionmentioning
confidence: 81%
“…Grin2b could compete with mmu_circRNA_34132 for binding to mmu-miR-29b-1-5p based on this study. Moreover, Nrf2 could downregulate miR-29b-1 through binding to specific ARE sites [53]. These findings suggested that mmu_circRNA_34132-mmu-miR-29b-1-5p-Grin2b interaction might play a role in neurodegenerative diseases that are regulated by Nrf2.…”
Section: Discussionmentioning
confidence: 81%
“…NRF2 binds to the sites of antioxidant responsive element (ARE) in the promoters of miR-125B1 and miR-29B1. NRF2 functionally promotes the expression of miR125B1, while NRF2 negatively controls miR-29B1expression2627. We next measured expression of both miR-125B1 and miR-29B1 in these two types of cells.…”
Section: Resultsmentioning
confidence: 99%
“…In acute myeloid leukaemia, a study showed that by decreasing the expression of miR-125B and increasing the expression of miR-29B, the cells showed increased sensitivity to apoptotic stimuli. 29 miR-125b-5p regulates GSH levels and hence acetaminophen-induced ALF by modulation of the Keap1-Nrf2 signalling pathway. However, Nrf2 may also contribute to further changes in miR-125b levels via a feedback loop as reported previously.…”
Section: Group (N = 3) Nrf2 Mir-125bmentioning
confidence: 99%